Tfam Knockdown Results in Reduction of mtDNA Copy Number, OXPHOS Deficiency and Abnormalities in Zebrafish Embryos - Otten, Auke B. C.; Kamps, Rick; Lindsey, Patrick; Gerards, Mike; Pendeville-Samain, Hélène; Muller, Marc; van Tienen, Florence H. J.; Smeets, Hubert J. M. (Frontiers in Cell and Developmental Biology, 2020)
High mitochondrial DNA (mtDNA) copy numbers are essential for oogenesis and embryogenesis and correlate with fertility of oocytes and viability of embryos. To understand the pathology and mechanisms associated with low mtDNA copy numbers, we knocked down mitochondrial transcription factor A (tfam), a regulator of mtDNA replication, during early zebrafish development. Reduction of tfam using a splice-modifying morpholino (MO) resulted in a 42%±17% decrease in mtDNA copy number in embryos at 4 days post fertilization. Morphant embryos displayed abnormal development of the eye, brain, heart and muscle, as well as a 50%±22% decrease in ATP production. Transcriptome analysis revealed a decrease in protein-encoding transcripts from the heavy strand of the mtDNA, and down-regulation of genes involved in haem production and the metabolism of metabolites, which appear to trigger increased rRNA and tRNA synthesis in the nucleoli. However, this stress or compensatory response appears to fall short as pathology emerges and expression of genes related to eye development are severely down-regulated. Taken together, this study highlights the importance of sufficient mtDNA copies for early zebrafish development. Zebrafish is an excellent model to manipulate the mtDNA bottleneck and study its effect on embryogenesis rapidly and in large numbers of offspring.